User perception at different architectural office setting: case study at International Islamic University Malaysia - Awang, Arita Hanim; Denan, Zuraini (IACSIT Press, 2012)
A widely accepted assumption is that better interior environment produces better results is designed with due importance to the nature of job and the individuals that are going to work in the office. A various studies have been made by previous researchers that have proved these co-relations but the same studies are still fairly new in Malaysian context. Architectural office therefore represent a challenged in nature of job and the individual as it need to be in the environment that is not just conducive environmnet that will supports creativity. The main objectives of this study are to find out the user perception of two different office layouts and get the user perception on the actual condition and other variables associates with office condition. For this purpose, a survey has been conducted with a control group of respondent using questionnaires.